2016
DOI: 10.5152/tpd.2016.4185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ectoparasites of Indigenous Chickens From Dalahu Region, Kermanshah Province, Iran

Abstract: Objective: Ectoparasitism is an important factor associated with the poor production of indigenous chickens. The present study was undertaken to estimate the prevalence and ectoparasite diversity in indigenous chickens of the Dalahu region in the western part of Kermanshah province, Iran. Methods: A total of 600 indigenous chickens (250 roosters and 350 hens) were randomly examined for the presence of different ectoparasites over the period April to September 2011. Ectoparasites were collected from different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 9 publications
3
20
2
Order By: Relevance
“…Waruiru et al (2017) also found that females had a significantly higher prevalence (58.8%) of ectoparasites compared to male ducks (41.2%). The stationary state of female wild ducks during the incubation of their eggs makes them more susceptible to ectoparasites which was described in chicken by Mirzaei et al (2016). In male ducks, mean intensity was the maximum of C. turbinatum (15 ± 2.23).…”
Section: Resultsmentioning
confidence: 93%
“…Waruiru et al (2017) also found that females had a significantly higher prevalence (58.8%) of ectoparasites compared to male ducks (41.2%). The stationary state of female wild ducks during the incubation of their eggs makes them more susceptible to ectoparasites which was described in chicken by Mirzaei et al (2016). In male ducks, mean intensity was the maximum of C. turbinatum (15 ± 2.23).…”
Section: Resultsmentioning
confidence: 93%
“…Ectoparasites hide in poor-hygiene poultry houses hence, the high prevalence of infestation in indigenous chicken production could be attributed to poor husbandry and lack of ectoparasite control measures, as chickens are known to roam around homesteads in a bid to scavenge for food leading to spread of ectoparasites when they come into contact with infested birds (Mungube et al, 2008;Sabuni et al, 2010). Recommended control measures for poultry keepers to curb ectoparasitism during outbreaks include good management practices and/or chemical control methods such as dusting, spraying and fumigation of the poultry using selected acaricides, larvicides and fumigants (Mirzaei et al, 2016).…”
Section: Research Articlementioning
confidence: 99%
“…Of 50 countries or regions in Asia as defined by the United Nations (9), studies on poultry mites were conducted in 10 countries; including Russia (10-12), China (13,14), Japan (15)(16)(17)(18)(19), Malaysia (20), Myanmar (21), Iran (22)(23)(24)(25)(26)(27)(28), India (29,30), Pakistan (31)(32)(33)(34), Vietnam (35), and Saudi Arabia (36). The poultry mite fauna comprises four orders: mesostigmata, sarcoptiformes, acariformes, and trombidiformes.…”
Section: Prevalence and Geographic Distributionmentioning
confidence: 99%
“…Likewise, our recent review indicated that the prevalence of PRM was higher in layer hens (85.2%) than in broilers (0.6%) ( 1 ). In Iran, PRM was also highly prevalent in the majority of farms ( 22 24 ). Of note, inspection of eight caged layer farms and four breeder flock premises yielded PRM in all of the facilities ( 22 ).…”
Section: Prevalence and Geographic Distributionmentioning
confidence: 99%
See 1 more Smart Citation